Thermodynamic property estimations for aqueous primary, secondary, and tertiary alkylamines, benzylamines, and their corresponding aminiums across temperature and pressure are validated by measurements from experiments - Kirtland J. Robinson; Jeffrey S. Seewald; Sean P. Sylva; Kristopher M. Fecteau; Everett L. Shock (Geochimica et Cosmochimica Acta, 2024)

Seasonal hydrologic and geologic forcing drive hot spring geochemistry and microbial biodiversity - Daniel R. Colman; Melody R. Lindsay; Annette Harnish; Evan M. Bilbrey; Maximiliano J. Amenabar; Matthew J. Selensky; Kristopher M. Fecteau; Randall V. Debes; Matthew B. Stott; Everett L. Shock; Eric S. Boyd (Environmental Microbiology, 2021)
Summary Hot springs integrate hydrologic and geologic processes that vary over short‐ and long‐term time scales. However, the influence of temporal hydrologic and geologic change on hot spring biodiversity is unknown. Here, we coordinated near‐weekly, cross‐seasonal (~140 days) geochemical and microbial community analyses of three widely studied hot springs with local precipitation data in Yellowstone National Park. One spring (‘HFS’) exhibited statistically significant, coupled microbial and geochemical variation across seasons that was associated with recent precipitation patterns. Two other spring communities, ‘CP’ and ‘DS’, exhibited minimal to no variation across seasons. Variability in the seasonal response of springs is attributed to differences in the timing and extent of aquifer recharge with oxidized near‐surface water from precipitation. This influx of oxidized water is associated with changes in community composition, and in particular, the abundances of aerobic sulfide‐/sulfur‐oxidizers that can acidify waters. During sampling, a new spring formed after a period of heavy precipitation and its successional dynamics were also influenced by surface water recharge. Collectively, these results indicate that changes in short‐term hydrology associated with precipitation can impact hot spring geochemistry and microbial biodiversity. These results point to potential susceptibility of certain hot springs and their biodiversity to sustained, longer‐term hydrologic changes.

Probing the geological source and biological fate of hydrogen in Yellowstone hot springs - Melody R. Lindsay; Daniel R. Colman; Maximiliano J. Amenabar; Kirsten E. Fristad; Kristopher M. Fecteau; Randall V. Debes; John R. Spear; Everett L. Shock; Tori M. Hoehler; Eric S. Boyd (Environmental Microbiology, 2019)
Summary Hydrogen (H 2 ) is enriched in hot springs and can support microbial primary production. Using a series of geochemical proxies, a model to describe variable H 2 concentrations in Yellowstone National Park (YNP) hot springs is presented. Interaction between water and crustal iron minerals yields H 2 that partition into the vapour phase during decompressional boiling of ascending hydrothermal fluids. Variable vapour input leads to differences in H 2 concentration among springs. Analysis of 50 metagenomes from a variety of YNP springs reveals that genes encoding oxidative hydrogenases are enriched in communities inhabiting springs sourced with vapour‐phase gas. Three springs in the Smokejumper (SJ) area of YNP that are sourced with vapour‐phase gas and with the most H 2 in YNP were examined to determine the fate of H 2 . SJ3 had the most H 2 , the most 16S rRNA gene templates and the greatest abundance of culturable hydrogenotrophic and autotrophic cells of the three springs. Metagenomics and transcriptomics of SJ3 reveal a diverse community comprised of abundant populations expressing genes involved in H 2 oxidation and carbon dioxide fixation. These observations suggest a link between geologic processes that generate and source H 2 to hot springs and the distribution of organisms that use H 2 to generate energy.